Modelling the yield of coriandrum sativum - Anak Bangga, Addison Juttie (2017)
The yield from coriander seed from an experiment conducted by Zoran (2017) are fitted into several models suggested by Brunner’s in the form of Brunner equation, Desorption model, Hot Ball Diffusion model, Broken and Intact Cells model, Shrinking Core model, and Esquivel Model. The performance of the four models are then examined using R-squared value and also Average Absolute Relative Deviation (AARD). The experiment is conducted at times 15, 30, 45, 60, 90, 120, 150, 180 and 240 min, pressures 100, 150 and 200 bar, temperatures 40, 55 and 70◦C, carbon dioxide flowrate of 0.2, 0.3 and 0.4 kg/h. Model fitting will be based on these conditions above. In terms of the actual yield of Coriander seeds, the highest yield is shown with the process condition of 200 bar and 55 Celsius and the lowest yield is with 100 bar and 55 Celsius. Based on the value of AARD values calculated from the Brunner model, Esquivel model, Desorption model and Hot Ball Diffusion model, it can be seen that on average, the Brunner model shows the lowest value with 0.280, Esquivel model with 2.720, Desorption model with 2.345 and Hot Ball Diffusion model with 5.959 for 200 bar and 55 Celsius. Therefore, it can be concluded that Brunner model performs the best at the test conditions.